Marital satisfaction and subjective well-being of adolescents who marry due to premarital pregnancy - Septiana, Ristie Suci Arya; Mukti, Patria; Andrianie, Prilya Shanty (Institut Agama Islam Negeri Langsa, 2024)
Marital satisfaction is an essential aspect of family life. Individuals who experience satisfaction in their marriage tend to exhibit positive emotions leading to happiness, which is associated with their subjective well-being encompassing their overall life satisfaction. Every individual naturally desires subjective well-being in their lives, including adolescents who marry due to unplanned pregnancies. Therefore, the aim of this research is to investigate the relationship between marital satisfaction and subjective well-being among adolescents who married because of unplanned pregnancies. The research methodology employed in this study is quantitative, with a total sampling technique used to select 64 adolescents who married due to unplanned pregnancies as participants. The data analysis method utilized in this study is the Pearson product-moment correlation. The analysis results reveal a correlation of r = -0.356 with a significance level of 0.004 (p < 0.05), indicating a significant relationship between marital satisfaction and subjective well-being. The positive direction of this relationship suggests that lower marital satisfaction corresponds to lower subjective well-being, and vice versa